Apelin secretion and expression of apelin receptors in 3T3-L1 adipocytes are differentially regulated by angiotensin type 1 and type 2 receptors - Than, Aung (2013)
Adipocytes play pivotal roles in regulating metabolism through secretion of a variety of adipokines, which in turn is regulated by other metabolic factors (e.g., insulin). Understanding the regulations of adipokine secretion is important because adipokines are implicated with metabolic disorders, such as, obesity and diabetes mellitus. Here, we investigated the regulatory roles of angiotensin II (AngII) on the secretion of apelin in 3T3-L1 adipocytes, and distinct signaling pathways mediated by AngII receptor type 1 (AT1) and type 2 (AT2) were revealed. It was found that activation of AT1 receptors stimulates apelin secretion in Ca2+, protein kinase C, and MAPK kinase dependent ways while activation of AT2 receptors inhibits apelin secretion through cAMP and cGMP dependent pathways. Furthermore, we demonstrate that the expression of apelin receptor (APJ) is also similarly regulated by AT1 and AT2 receptors. Finally, a detailed AngII signaling map is proposed.